Estudio experimental de procesos de calentamiento y enfriamiento. Resultados e implicaciones didácticas - Fraile Delgado, J. J.; García Hourcade, J. L.; García Montes, J.; Rodríguez de Ávila, C.; Rubio Regueiro, J. L. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
A detailed experimental study on different processes of heating and cooling allows to deduce that temperature variation, in these processes, in the course of time is not always the same, but it depends, to a great extent, on how the process is carried out. So to confuse the T-Q relations (always lineal) with T-t relations (dependent on the process) is a mistake that is necessary to avoid in our classes.